1990
DOI: 10.1210/jcem-71-5-1131
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Thyroid Autoimmune Disease: Molecular Analysis of HLA-D Region Genes Identifies New Markers for Goitrous Hashimoto's Thyroiditis

Abstract: Hashimoto's thyroiditis has been shown to be associated with the HLA-specificities DR4 and DR5. Since former association studies yielded variable results, we used novel molecular typing methods to assess predisposing immunogenetic factors. Gene analysis of the HLA-DR-DQ and tumor necrosis factor region was performed in a group of Hashimoto's thyroiditis patients and randomly chosen controls using standards and nomenclature of the 10th International Histocompatibility Workshop. Genomic DNA of patients and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
4

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 0 publications
1
34
0
4
Order By: Relevance
“…Many of the immunological diseases that occur with AIH, namely autoimmune thyroiditis, RA, Sjogren's syndrome and IBD have been associated with this extended haplotype [30][31][32][33][34][35][36] . The clustering of the CAIDs in AIH may suggest the shared genetic and immunological susceptibility [37,38] .…”
Section: Effects Of Aih Types Age Gender and Genetic Backgroundmentioning
confidence: 99%
“…Many of the immunological diseases that occur with AIH, namely autoimmune thyroiditis, RA, Sjogren's syndrome and IBD have been associated with this extended haplotype [30][31][32][33][34][35][36] . The clustering of the CAIDs in AIH may suggest the shared genetic and immunological susceptibility [37,38] .…”
Section: Effects Of Aih Types Age Gender and Genetic Backgroundmentioning
confidence: 99%
“…Earlier studies showed an association of goitrous HT with HLA-DR5 and of atrophic HT with HLA-DR3 [36,37]. Later studies have reported association of HT with HLA-DR3, HLA-DR4, or HLA-DR5 in Caucasian patients [38][39][40][41][42]. However, a recent study has shown that a molecular signature of HLA-DR pocket, determined by specific amino acids, confers a significant risk for the development of HT across HLA-DR alleles [35,43].…”
Section: Etiology and Genetics Of Htmentioning
confidence: 99%
“…Early studies showed an association of goitrous HT with HLA-DR5 (7) and of atrophic HT with -DR3 (8). Later studies have reported associations of HT with HLA-DR3 (9, 10), -DR4 (11,12), or -DR5 (13) in Caucasians. The prevalent assumption is that these discrepancies are caused by the wide variation in the diagnostic criteria for HT ranging from the simple presence of thyroid autoantibodies with focal lymphocytic infiltration to the presence of goitrous or atrophic thyroiditis characterized by gross thyroid failure (14).…”
mentioning
confidence: 99%